Prevalence and predictors of overweight and obesity among women of childbearing age in the province of Essaouira, Morocco - Abdelmounaim Manoussi; Nezha Nacer; Imane Kajjoune; Abdellatif Baali; Hakima Amor; Nadia Ouzennou (BMC Public Health)
Abstract Low- and middle-income countries are facing a rapid increase in nutritional problems, particularly in Africa, where undernutrition, overweight and micronutrient deficiencies coexist, creating a double burden of malnutrition and a challenge to public health policies. In this context, Morocco stands out for its early nutritional transition, characterized by a moderate prevalence of overweight and undernutrition and elevated levels of micronutrient deficiencies. The aim of this study was to assess the weight status of women of childbearing age and identify its determinants to suggest ways to improve it. The study was conducted in the province of Essaouira in Morocco, which is characterized by a predominance of rural areas and multidimensional poverty. We conducted a quantitative cross-sectional survey of 1,466 married women of childbearing age via stratified random sampling. Data were collected via questionnaires and anthropometric measurements; we applied the WHO curves to classify BMI. Data entry and statistical processing were performed via SPSS® v. 26. The results show that women’s weight status is worrisome, with an average BMI of 26.4 kg/m². The prevalence of overweight was 61.6% (BMI ≥ 25 kg/m2), with 17.9% of women being obese. Bivariate analysis revealed that age, education level, socioprofessional activity, family structure, household income and parity were significantly associated with overweight. Binary logistic regression confirmed that women’s age and level of education are major determinants of overweight/obesity. There is a need to strengthen public health policies aimed at reducing overweight and obesity among women of childbearing age in Morocco, with an emphasis on nutrition education and monitoring their weight status throughout their reproductive lives.